Factors Influencing Exclusive Breastfeeding at 4 Months Postpartum in a Sample of Urban Hispanic Mothers in Kentucky. (May 2015) - Linares, Ana Maria; Rayens, Mary K.; Dozier, Ann; Wiggins, Amanda; Dignan, Mark B.
Background: Although Hispanic mothers in the United States have slightly higher rates of breastfeeding initiation than the national average, they are more likely to supplement with formula. Objectives: To describe infant feeding decisions in a sample of 72 urban Hispanic mothers and assess whether demographic and personal factors influence exclusive breastfeeding (EBF) status at 4 months postpartum. Methods: The study was longitudinal and included assessments during pregnancy, in the hospital following childbirth, and monthly up to 4 months following birth. Results: Nearly all of the 72 mothers were breastfeeding at discharge after the birth of their infant (94%); half of these were EBF. By 2 months postpartum, the rate of EBF had declined to 26%, dropping to 22% by 4 months. Significant predictors of EBF status at 4 months included the baseline indicator for mother's partner as the most important person in life (adjusted odds ratio [AOR], 5.42; 95% confidence interval [CI], 1.03-28.66) and breastfeeding self-efficacy score at 1 month (AOR, 1.20; 95% CI, 1.07-1.34). Conclusion: These findings have particular relevance in this population, given the high rate of breastfeeding initiation coupled with breastfeeding self-efficacy being a modifiable factor. Support during pregnancy and postpartum, including consultation with a lactation consultant, may increase the self-efficacy of EBF in this low-income population, leading to higher rates of extended EBF among Hispanics.